ANALISIS ESTIMASI BIAYA DAN WAKTU PROYEK PADA GEDUNG 5 LANTAI UNIVERSITAS X DI SURABAYA - Ricardo Salim; Cahyono, M. Shofwan Donny; Norman Ray (Seminar Nasional Ilmu Terapan, 2024)
construction industry is known for its complex and dynamic nature, making project management a very important aspect to ensure time and cost effectiveness. Although project management is very important, many construction projects in Indonesia still experience delays, which can result in significant financial losses and damage to the company's good name. This research aims to examine the application of descriptive analysis in analyzing construction project management practices inIndonesia, with a focus on identifying schedule and cost analysis estimates at University X in Surabaya. This research uses a qualitative research approach, involving interviews with construction parties directly involved in the field. The data collected was then analyzed using descriptive analysis, which involved scheduling estimates using Microsoft Project tools. The research results show that poor planning, insufficient resources, and ineffective communication are among the factors that contributeto construction project delays. The research also found that the effective schedule and cost by eliminating delay factors on this project was 32 weeks and IDR 33,566,78,158, then methods and alternatives that can be applied according to actual conditions in the field are accelerating work that is on the critical path. The research results show that the implementation of these strategies and methods can produce a project schedule that is 2 weeks faster. The contributions of this research includeproviding an in-depth look at the factors that contribute to construction project delays and proposing practical strategies to speed up schedules. The results of this research can provide information to project managers and construction practitioners on how to improve their project management practices and achieve better results.